On the importance of pyrolysis for inkjet-printed oxide piezoelectric thin films. Issue 11 (14th February 2020) - Godard, Nicolas; Mahjoub, Mohamed Aymen; Girod, Stéphanie; Schenk, Tony; Glinšek, Sebastjan; Defay, Emmanuel
Abstract : Inkjet printing is an attractive low-cost method for the deposition of piezoelectric lead zirconate titanate thin films. Pyrolysis temperature and time are crucial processing parameters to obtain dense layers with state-of-the-art properties. Abstract : Inkjet printing (IJP) is an attractive technology for the low-cost fabrication of functional metal oxide thin films, such as piezoelectric lead zirconate titanate (PZT). Implementation of the well-established chemical solution deposition method for PZT films in the IJP process comes with challenges, which were the focus of several works in the field. However, adequate pyrolysis conditions are also required for the complete elimination of organic residues from the layers before crystallization. Thanks to an original technique based on infra-red spectroscopy, the present study draws the correlation between the amount of residual organics in pyrolyzed inkjet-printed layers on platinized silicon and the porosity and functional properties of the final films. Pyrolysis at 475 °C for 3 min afforded dense {111}-textured 200 nm-thick PZT layers after crystallization at 700 °C, with state-of-the-art electrical properties ( P r = 23 μC cm −2, E c = 60 kV cm −1, ε ′ = 1000 and tan  δ = 0.04). Potential of inkjet printing technology for piezoelectric devices is demonstrated through a simple energy harvesting device, with a 5.8 μW power output for a 6 kΩ resistive load.